Fine-Tuning Climate Resilience in Marine Socio-Ecological Systems: The Need for Accurate Space-Time Representativeness to Identify Relevant Consequences and Responses - Saldívar-Lucio, Romeo; Trasviña-Castro, Armando; Jiddawi, Narriman; Chuenpagdee, Ratana; Lindström, Lars; Jentoft, Svein; Fraga, Julia; de la Torre-Castro, Maricela (Frontiers in Marine Science, 2021)
Climate change triggers a wide mosaic of regional and local responses, often different to the large-scale variability in magnitude and direction. Because of the psychological connections (cognitive and emotional) with the frequency, intensity and age of a climatic event, people may have the capacity to recognize key variations at lower scales, especially those from which they perceive risk. Yet, the anticipatory actions and social engagement to respond or adapt to climate change are difficult to achieve, mostly when there exists a long psychological distance to climatic phenomena. Research about climate change communication provides clues about the relevance of place-based discussion to gauge risk perception and improve response protocols, their design and prioritization. It argues that strategies and actions required to face climate risks may widely differ depending on the scale and accuracy of the local representations displayed during discussions of climate impacts. This work examines how local attributes (from climate to social) operate and control place-specific risks and priorities, by comparing coastal communities in two locations, Cabo Pulmo, Mexico and Zanzibar, Tanzania, which are subject to different climate dynamics. This paper discusses the need to identify relevant climate risks/responses at the local level and how psycho-social factors (e.g., psychological distance, collective memory, and social engagement) may operate positively for building climate resilience. We also illustrate a workflow to increase and enhance collaboration between researchers and local people by promoting dialogue, participation and narratives that rigorously consider the local knowledge.